A study on 24 hours ambulatory blood pressure monitoring among hypertensive patient attending Family Medicine Clinic HUSM - Juwita, Shaaban (Pusat Pengajian Sains Perubatan, 2012)
Hypertension is a common and an important modifiable risk factor for cardiovascular disease, cerebrovascular and renal disease. Although the percentage of patients who are treated for hypertension has increased, the percentage of those who demonstrate control of blood pressure has declined. The objectives of this study were to describe the circadian blood pressure profile of hypertensive patients attending Family Medicine Clinic HUSM. This is a cross sectional study conducted from 1'1 January 2008 to 301 h June 2008 among hypertensive patients attending Family Medicine Clinic HUSM. All patients who fulfilled inclusion criteria were selected via systematic random sampling. Schiller BR-102 plus was put I, • on patients to get 24 hours BP reading. Mean of two office blood pressure were also taken. Non dippers are defined as systolic or diastolic nocturnal drop of less than 10%. Analysis was done using SPSS Version 12. A result of 105 patients were able to be recruited with 59 (56.2%) males and 46 (43.8%) were female with mean age of 51.8 (SD 9.34) years old. The patients' mean 24 hours SBP and DBP .. were 128.4 (SD 12.7) mmHg and 79.7 (SD 8.74) mrnHg respectively. Mean daytime SBP and DBP were 132.1 (SD 11.72) mmHg and 82.4 (SD 9.41) mmHg while for the mean night time SBP and DBP were 123.3 (SDI2.78) mmHg and 76.2 (SD9.01) mmHg. Percentage of non dippers were 68.6% for systolic and 61.9% for diastolic. Percentage of uncontrolled systolic and diastolic 24 hours ABPM were 26.7% and 23.8%, respectively and percentage of uncontrolled diastolic night time blood pressure was 56.2%. Percentage of uncontrolled office blood pressure was high 57.1% systolic and 61.0% diastolic and the difference between office and 24 hours were statistically significant. However the simple logistic regression analysis done to look for the association of cardiovascular risk factor and non dippers were not significant. In conclusions the mean 24 hours and daytime ambulatory blood pressure were normal but the mean diastolic night time was above normal value. Majority of the patients were categorized as non dippers. The percentage of uncontrolled office blood pressure was high compared to 24 hours ABPM. Therefore using ambulatory blood pressure was clinically and practically important to get a better understanding of blood pressure fluctuations over 24 hour periods compared to simple clinical measurements